2021
DOI: 10.1002/mrd.23459
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of sex‐biased and differentially expressed miRNAs in gonadal developments of the Chinese mitten crab, Eriocheir sinensis

Abstract: MicroRNA (miRNA) is a posttranscriptional downregulator that plays a vital role in a wide variety of biological processes. In this study, we constructed five ovarian and testicular small RNA libraries using two somatic libraries as reference controls for the identification of sex‐biased miRNAs and gonadal differentially expressed miRNAs (DEMs) of the Chinese mitten crab, Eriocheir sinensis. A total of 535 known and 243 novel miRNAs were identified, including 312 sex‐biased miRNAs and 402 gonadal DEMs. KEGG pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…A total of 152 differentially expressed miRNAs were identified ( Figure S8; Table S10 ). Based on the literature report [ 27 , 28 ], thirteen sex-related miRNAs were identified in this study, among which bantam-3p, miR-34, miR-133, miR-263a, and miR-263b were differentially expressed ( Table 1 ). Among them, the expression changes of miR-133, miR-263a, and miR-263b were opposite after GsiRNA and YsiRNA injection ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 152 differentially expressed miRNAs were identified ( Figure S8; Table S10 ). Based on the literature report [ 27 , 28 ], thirteen sex-related miRNAs were identified in this study, among which bantam-3p, miR-34, miR-133, miR-263a, and miR-263b were differentially expressed ( Table 1 ). Among them, the expression changes of miR-133, miR-263a, and miR-263b were opposite after GsiRNA and YsiRNA injection ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…To better understand the regulatory roles of the differentially expressed miRNAs, GO enrichment and KEGG pathway analyses of the target genes of differentially expressed miRNAs were performed, and many GO terms and KEGG pathways were enriched ( Table S12 ). The KEGG pathway analysis showed that target genes were enriched in the MAPK signaling pathway, which is a sex-related pathway [ 28 ]. The GO analysis indicated that the target genes were statistically enriched in more than 100 GO terms ( Figure S9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Reads of the second peak in Hai-05 and Hai-19 may belong to PIWI-interacting RNAs (see also Ord et al, 2020). Two peaks shown in the length distribution of small RNA reads have also been documented in other studies (e.g., Fu et al, 2020;Luo et al, 2021). Because miRNAs typically have ~22 nts in length, we only retained reads of 18-26 nts, resulting in an average of 8,266,875 reads per sample (Dryad file T3).…”
Section: Identification Of Mirnas In R Affinismentioning
confidence: 99%
“…The well-known function of miRNAs it the regulation of gene expression, which is involved in immune system, differentiation and proliferation, growth and development, tumorigenesis, and cell death (O'Connell et al, 2010). To date, miRNAs have been identified and characterized in several crab species including Chinese mitten crab Eriocheir sinensis (Song et al, 2014;He et al, 2015;Chen et al, 2020;Fu et al, 2021;Luo et al, 2021), mud crab Scylla paramamosain (Li et al, 2013;Jia et al, 2018;Wang et al, 2018;Waiho et al, 2019;Jin et al, 2020;Lai et al, 2020), swimming crab Portunus trituberculatus (Ren et al, 2016;Meng et al, 2018Meng et al, , 2020, and freshwater crab Sinopotamon henanense (Xu et al, 2019). However, most of the studies often evaluated specific tissue expressed miRNAs in crabs.…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitously expressed piRNAs were discovered in the soma and germ lines of Annelida, Cnidaria, Echinodermata, Arthropoda, and Mollusca, but underwent tremendous changes in the Chordata (Huang et al, 2021). Interestingly, abundant piRNA-sized reads with a length of 24-31 nt were detected in the gonadal tissues of crabs (He et al, 2015;Meng et al, 2018;Luo et al, 2021), but very few studies have noticed these piRNAs in crabs (Waiho et al, 2020). Crabs, as important aquaculture species, have high commercial value as a food source.…”
Section: Introductionmentioning
confidence: 99%